2017
DOI: 10.1038/s41598-017-11215-y
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional comparative study of gut bacterial community of Indian and Finnish children

Abstract: The human gut microbiome plays a crucial role in the compositional development of gut microbiota. Though well documented in western pediatrics population, little is known about how various host conditions affect populations in different geographic locations such as the Indian subcontinent. Given the impact of distinct environmental conditions, our study assess the gut bacterial diversity of a small cohort of Indian and Finnish children and investigated the influence of FUT2 secretor status and birth mode on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 75 publications
2
24
0
Order By: Relevance
“…The clinical significance of these findings obtained from a relatively small number of subjects is open to debate since the role of the bacteria in breast milk in mediating the beneficial effects of breastfeeding or determining the child's health remains poorly understood. Nonetheless, we and others have reported that the mode of birth markedly influences the developing gut microbiota both in the neonatal period and later in childhood (1921). This may at least partially explain the epidemiological association between birth by cesarean section and increased incidence of non-communicable diseases later in life (22).…”
Section: Discussionmentioning
confidence: 75%
“…The clinical significance of these findings obtained from a relatively small number of subjects is open to debate since the role of the bacteria in breast milk in mediating the beneficial effects of breastfeeding or determining the child's health remains poorly understood. Nonetheless, we and others have reported that the mode of birth markedly influences the developing gut microbiota both in the neonatal period and later in childhood (1921). This may at least partially explain the epidemiological association between birth by cesarean section and increased incidence of non-communicable diseases later in life (22).…”
Section: Discussionmentioning
confidence: 75%
“…Unfortunately, the explicit processing features of the food ingested by the investigated subjects have not been explored in these studies. Furthermore, gut microbiomes from different parts of the world often display a very different composition from those from Western subjects [see for recent studies, e.g., (Kumbhare et al ., ; Chauhan et al ., ; Dubois et al ., )]. As for younger subjects, Bacteroidaceae and strictly anaerobic Firmicutes dominate the colon microbiome of present‐day centenarians, but the species are often different from those in young people (and remember differences in mummies microbiota, discussed previously).…”
Section: Microbiota At Old Agementioning
confidence: 99%
“…As a consequence, this may have a strong impact on the clustering of microbiomes into genomes belonging to specific species and even individual strains that interact with the corresponding surfaces, a fact that has seldom been taken into account. Indeed, a recent study found a strong influence of the secretor status in widely different populations (Kumbhare et al ., ). All this casts doubt on the validity of the interpretations stemming from a major fraction of microbiome studies.…”
Section: Genomes and Evolution: The Gut Microbiota Of Man And Great Apesmentioning
confidence: 99%
“…Feeding patterns and strong food preferences of ASD children for nutrient-poor starchy foods while rejecting fruits, vegetables, and proteins may lay the foundation of an abnormal GM. The high prevalence of ASD in some countries has been correlated with typical carbohydrate rich diet and consequently predominance of genera Prevotella and Megasphaera [25]. Therefore, understanding how these changes affect human GM suggests that early dietary habits have a more complex effect on the metabolic programming of a child than previously anticipated.…”
Section: Disruptions Of Microbial Colonization In Autism Spectrum Dismentioning
confidence: 99%